La Gobernanza en el Funcionamiento de los Servicios del Sistema de Gestión Ambiental de Playas de Montevideo (Uruguay) - Marchese, Luidgi; Conde, Daniel; Polette, Marcus (Sustainability in Debate, 2013)
Internationally beaches are an important factor of tourism production. As a fragile space of ecological and environmental balance, its management is essential. This study was conducted through semi-structured in-depth interviews, seeking to analyze the operation of the Environmental Management System of beaches (EMS) in Montevideo and the model of governance and development that the EMS is working in order to contribute to a more integrated and sustainable management of these environments. It was identified that the operation of the governance model of the EMS implemented started from a model “top-down”. Consequently, at the beaches it’s possible to identify uses and activities that compromise environmental quality. It was concluded that it´s necessary to improve governance EMS, with the goal that the commitment of the members, and the power and support of the EMS are improved, seeking to achieve an efficient and effective management for the sustainability of the coast in general.